Re-Vitalizing Worthiness: - Evelyn Gordon; John R. Cutcliff; Chris Stevenson (Grounded Theory Review: An International Journal)
Rates of suicide and suicidality have risen in many countries in recent years and in Ireland this trend has been particularly evident among young men (NOSP, 2005), focusing attention on how best to respond to this group. Although mental health professionals have been identified as a key group to respond to the suicidal person, it has been suggested that they are ill-prepared for working in this area (Maltsberger & Goldblatt, 1996; Ting et al., 2006; Cutcliffe & Stevenson, 2007). This study aimed to address these issues by developing a theoretical understanding of suicidality among young men to inform professional practice. Using Classic Grounded Theory (Glaser & Strauss, 1967), in-depth one-to-one interviews were conducted with 17 young men who had been suicidal and had been in contact with the mental health services. The substantive theory that emerged, re-vitalizing worthiness in overcoming suicidality, describes the psychosocial process that young men go through to resolve their main concern, which centres on their painful pull between life and death. Overcoming suicidality involves moving from a death orientation to a life orientation while incorporating the inevitability of death into their new sense of being. This transition entails identity re-configuration whereby young men emerge as individuals of value who are deserving of life. The process is influenced significantly by personal insights and interpersonal interactions that influence their suicide trajectories and life pathways. The theory contributes to the fields of suicidology and mental health by providing a theoretical understanding of overcoming suicidality and identifying professional and social practices that facilitate and impede this process.